Hadits-Hadits Tentang Materi Pendidikan Yang Paling Diprioritaskan Untuk Menjadi Landasan Dalam Membangun Jiwa Anak Didik - Wismanto Wismanto; Ardiansyah Ardiansyah; Junindra Darisky Saputra; Zamzami Zulfa (Jurnal Budi Pekerti Agama Islam, 2024)
Education plays a crucial role in enhancing human faith in Allah SWT. This is marked by the significant number of verses in the Quran and Hadith of the Prophet related to education or knowledge. This study aims to describe the prioritized material to serve as the foundation in nurturing the souls of students from the perspective of the Prophet's Hadith in the two authentic books concerning faith. Using a literature approach, the author concludes that the goal of education in the two authentic books is devotion to Allah, instilling noble character in students, promoting a good life in this world and the hereafter, and shaping a strong believer's personality.